Murder at St. Winifred's Academy - Griffo, J. D. (Griffo, J. D. Ferrara family mystery., 2021)
"Alberta can hardly believe it. Her childhood screen idol, 1950s Hollywood starlet Missy Michaels, has signed up for the local Tranquility Players revival of the classic Arsenic and Old Lace. But before Missy memorizes a single line, she's found dead in her dressing room wrapped in lace and clutching a bottle of arsenic. The ultimate drama-queen suicide? Everyone thinks so--except Alberta. A Ferrara woman knows murder when she sees it"--